Medidas provisórias do Tribunal Internacional do Direito do Mar: a abordagem da precaução como padrão de aplicação do requisito da urgência - Gustavo Leite Neves da Luz (2022)
The work examines the standard of application of the requirement of urgency in the provisional measures prescribed in cases related to the protection of the marine environment in the International Tribunal for the Law of the Sea (ITLOS). The dissertation seeks to answer the problematic question whether in the provisional measures prescribed for the protection of the environment in ITLOS, is possible to determine a standard of application for the requirement of urgency through the precautionary approach. With this purpose, its course will be divided into three chapters. The first one will analyze the powers and limits for granting provisional measures by the tribunals established on the basis of the United Nations Convention on the Law of the Sea (UNCLOS), which will address the history, concepts, characteristics, requirements and purposes of provisional measures. In the second one, it will be presented the precautionary principle and its relation to the prescription of provisional measures, in which it will be verified especially which form the precaution is applied by ITLOS, as a principle or approach, which, based on the evidence presented, it is verified that ITLOS applies the approach. With such bases established, in the third chapter it will finally be analyzed if the requirement of urgency in the prescription of provisional measures to protect the marine environment has a pattern of application through the precautionary approach. The hypothesis verified is that based on the judicial decisions presented by ITLOS in its cases which provisional measures were prescribed for the purpose of environmental protection the precautionary approach does not provide a standard of application for the requirement of urgency, as in the analysis of the requirement it is not possible to meet all the criteria necessary for its joint verification with the approach.